The Role of High Schools in Central Kalimantan in Developing Islamic Religious Education for Adolescents: A Field Review in the Technological Era - Muliatul, Muliatul; Sidqi, Nasiruddin; Mazrur, Mazrur (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In the era of rapidly developing technology, the adaptation of the Islamic Religious Education (PAI) paradigm is crucial to improve the values of religious education in adolescents. Digital transformation has affected the way adolescents access Islamic religious information and practices, triggering the need to reform the PAI paradigm to remain relevant and effective. The purpose of this study is to determine the Role of Senior High Schools (SMA) in Central Kalimantan in Developing Islamic Education for Adolescents. Field Overview in the Age of Technology. This research uses a descriptive method of analysis with a qualitative type. The results of this study show that one of the schools, Al-Khair Islamic High School in Central Kalimantan, displays a strong commitment in the development of Islamic religious education. This is evidenced by the number of students as many as 500 people and high teacher qualifications, this school provides great potential in providing quality Islamic religious education. The use of technology in learning, collaboration with religious institutions, and structured evaluation systems are concrete efforts made by schools. Despite challenges such as a lack of understanding of religious teachers' technology and limited internet access, Al-Khair Islamic High School has taken continuous improvement measures, such as technology training for religious teachers. Thus, this school shows seriousness in meeting the demands of the times and improving the quality of Islamic religious education for the younger generation in Central Kalimantan.